If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16(x + 2) + -8 = 6x + 24 Reorder the terms: 16(2 + x) + -8 = 6x + 24 (2 * 16 + x * 16) + -8 = 6x + 24 (32 + 16x) + -8 = 6x + 24 Reorder the terms: 32 + -8 + 16x = 6x + 24 Combine like terms: 32 + -8 = 24 24 + 16x = 6x + 24 Reorder the terms: 24 + 16x = 24 + 6x Add '-24' to each side of the equation. 24 + -24 + 16x = 24 + -24 + 6x Combine like terms: 24 + -24 = 0 0 + 16x = 24 + -24 + 6x 16x = 24 + -24 + 6x Combine like terms: 24 + -24 = 0 16x = 0 + 6x 16x = 6x Solving 16x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16x + -6x = 6x + -6x Combine like terms: 16x + -6x = 10x 10x = 6x + -6x Combine like terms: 6x + -6x = 0 10x = 0 Divide each side by '10'. x = 0.0 Simplifying x = 0.0
| x-9y=0 | | 1+2b=399 | | a+14=5a-2 | | 8(6f-14)-7(12-5f)+(23f+2)-(2f+65)=0 | | 13s+5=14s+13 | | -7y=-6y+10 | | -2s+6=-5s+12 | | (7x^3+8x-11)+(3x^2-x+8)= | | -14y+7=-13y+1 | | b+0.5=2 | | 4-2(d+7)-(3d+5)=2d+(4d-9+3d)-(d-3) | | 2x+10=x-63 | | x=1+2x | | 3x^3+3x^2=27x | | 8X-6=42+6X | | 5x^2+10x+13=6x^2+4x | | 5x^2+10x-18=6x^2+4x | | 5x^2+10x-3=6x^2+4x | | 5x^2+10x-13=6x^2+4x | | -7x+4x-11=22 | | 3(x+7)=5x-7 | | v^2-10v+21=0 | | v^2-10+21=0 | | 2(x-5)+3x=20 | | 6c-4=24-c | | -3y+4=-5y-6 | | x^2+16x=-3 | | 4x^3-6x^2=4x | | 16t-4=8t | | 2x-26=x+2 | | 7-6(c-1)+3(3-4c)=7+(7c-4) | | 8C-C+6=48 |